Implementasi Metode Mutaba'ah dalam Menumbuhkan Motivasi Siswa Menghafal Al-Qur'an di SDN 52 Parupuk Tabing - Putri, Archi Armelya; Wiza, Rahmi (AS-SABIQUN, 2023)
The purpose of this study was to determine the planning, implementation and evaluation of the Mutaba'ah method in motivating students to memorize the Al-Qur'an in class V SDN 52 Parupuk Tabing. The methodology used in this study is qualitative with a descriptive approach. The data obtained to support this research are in the form of observations, interviews and documentation. The research results obtained are as follows: 1. Planning In this first step it is known that the planning of the Tahfidz Juz 30 program uses the 7-step Mutaba'ah method, namely: a) preparation of initial planning, b) consideration of program objectives, c) determination of method, d) determining the place and time, e) determining the learning objectives, f) determining the person in charge of the criteria of a teacher and g) conveying the expectations of the Tahfidz Juz 30 program 2. Implementation of the Tahfidz Juz 30 program uses the Mutaba'ah method. Implementation includes the steps that teachers apply and the limitations of the implementation process they face. 3. The Tahfidz juz 30 program will be evaluated in two stages using the Mutaba'ah method. The first assessment is from the teacher, this assessment is weekly assessment and end of semester assessment. The second assessment is then an assessment carried out by the students themselves, where students can measure their own memory.